MODEL PEMBELAJARAN PROBLEM SOLVING DI PONDOK PESANTREN - Siti Hajah Khalifaturohma; Zahrotul Mufida (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2020)
The Islamic Boarding School is the oldest education institution in Indonesia. It doesn’t hold on firmly to the classical method. But. It also follows the development. Until the emergence terminology of modern Islamic Boarding School. Including It’s learning model which has followed to era development. But. It still maintains the Islamic Boarding School’s values. One is problem solving earning model. The discussion this time will talk over related to problem solving as the authentic concept and tried to be compared with the Islamic Boarding school  problem solving that’s called bahtsul masail. The result of discussion indicates that bahtsul masa’il is more classic than problem solving. But. bahstul masa’il provides  the problem solving more complex. It doesn’t just based on the logical law. But also it must basically principled to Al Quran and Hadist and other instinbat methods.